Cyclooxygenase-2-Prostaglandin E2 pathway: A key player in tumor-associated immune cells - Jin, Kaipeng; Qian, Chao; Lin, Jinti; Liu, Bing (Frontiers in Oncology, 2023)
Cyclooxygenases-2 (COX-2) and Prostaglandin E2 (PGE2), which are important in chronic inflammatory diseases, can increase tumor incidence and promote tumor growth and metastasis. PGE2 binds to various prostaglandin E receptors (EPs) to activate specific downstream signaling pathways such as PKA pathway, β-catenin pathway, NF-κB pathway, and PI3K/AKT pathway, all of which play important roles in biological and pathological behavior. Nonsteroidal anti-inflammatory drugs (NSAIDs), which play as COX-2 inhibitors, and EP antagonists are important in anti-tumor immune evasion. The COX-2-PGE2-EP pathway promotes tumor immune evasion by regulating myeloid-derived suppressor cells, lymphocytes (CD8+ T cells, CD4+ T cells and natural killer cells), and antigen presenting cells (macrophages and dendritic cells). Based on conventional treatment, the addition of COX-2 inhibitors or EP antagonists may enhance immunotherapy response in anti-tumor immune escape. However, there are still a lot of challenges in cancer immunotherapy. In this review, we focus on how the COX-2-PGE2-EP pathway affects tumor-associated immune cells.